A corpus‐based method for identifying word class in an English lexified extended pidgin. Issue 2 (14th December 2019) - FitzGerald, Sarah
Abstract: This paper outlines an innovative corpus‐based method for establishing word class using as a case study the verbal status of the locative copula in Cameroon Pidgin English. The corpus‐based methodology outlined here uses a combination of distributional, sociolinguistic, and frequency analysis to establish that the Cameroon Pidgin English locative copula, deiy, is a verb and in doing so outlines a blueprint for establishing word class in under described languages. Pidgin creole languages are often under described and identifying the word class of multifunctional words can be particularly challenging. The methodology presented here can resolve such ambiguity by basing the classification on the language in which the word occurs rather than on typological generalisations. This corpus‐based methodology has wide ranging applicability and could be especially useful in establishing word class in lesser described world English varieties and pidgin creole languages.